Energetic metabolic profile of ewes presenting low body condition score induced to subclinical hypocalcemia in early postpartum - Schmitt, Eduardo; Maffi, Andressa S.; Raimondo, Raquel F. S.; Lima, Marcio E.; Hoffmann, Dustin A. C.; Farofa, Tiago S.; Montagner, Paula; Rincón, Joao A. A.; Del Pino, Francisco A. B.; Corrêa, Marcio N. (Austral Journal of Veterinary Sciences, 2018)
The aim of the present study is to assess plasma concentrations of metabolites related to energy balance in ewes showing low body condition score (BCS) induced to subclinical hypocalcemia in early postpartum. Sixteen crossbred ewes (Ideal x Corriedale) presenting BCS <3 were divided in two groups: 1) control group (n = 9), which received no treatment, and 2) hypocalcemia group (n = 7), which was subjected to twelve hours of induced subclinical hypocalcemia through intravenous Na2EDTA infusion six hours postpartum. Ionized calcium levels were monitored and kept between 0.62 and 0.87 mmol/L. All ewes were subjected to daily blood sampling for five days in order to set the postpartum metabolic profile. There was no interaction between day and treatment in total and ionized calcium concentrations (P>0.05), whereas the mean concentrations of these marks after five days were lower in the hypocalcemia group (P<0.05). However, neither the mean group were different at glucose, non-esterified fatty acids, beta-hydroxybutyrate and insulin (P>0.05) level. These results evidence that, despite the subclinical hypocalcemia induction at early postpartum, ewes presenting low body condition do not change the concentrations of energy balance-related metabolites in the following five days.